The effect of psychological empowerment on clinical nurses’ thriving at work: the mediating role of voice behavior - Jiehao Zhuang; Xuanhao Fan; Niu Yang; Ziyi Xiong; Zhongqing Chen; Jiangfeng Pu; Zhanghao Xie; Huajun Wang; Binbin He; Tiemei Shen; Huigen Huang (BMC Nursing)
Abstract Background Facing the shortage of nurses and the surge in demand for nursing services, factors affecting the stability of the nursing workforce require urgent attention. Thriving at work, a positive psychological state, can improve the quality of nursing services and promote the development of the nursing workforce. Therefore, this study aims to determine the impact of psychological empowerment on nurses’ thriving at work and confirm the mediating role of voice behavior. Methods This cross-sectional study recruited 590 clinical nurses from 11 hospitals in Guangdong Province, China. Data were collected using a demographic questionnaire, the Psychological Empowerment Scale, the Voice Behavior Scale, and the Thriving at Work Scale. Descriptive statistics, Pearson’s correlation, and mediation analysis via SPSS 26.0 with Hayes’ PROCESS Macro (Model 4) were employed for data analysis. Results The clinical nurses’ scores for psychological empowerment were 43.56 ± 7.21, for voice behavior were 34.45 ± 7.37, and for thriving at work were 35.75 ± 6.81. Pearson’s correlation analysis revealed significant positive relationships: psychological empowerment was strongly correlated with voice behavior (r = 0.693, p < 0.01), with thriving at work (r = 0.735, p < 0.01), and voice behavior was also positively correlated with thriving at work (r = 0.666, p < 0.01). Furthermore, voice behavior was confirmed to mediate the relationship between psychological empowerment and thriving at work, with a significant mediating effect of 0.197 that accounted for 28.35% of the total effect. Conclusions This study confirms the validity of the “Resources → Individual Agentic Work Behaviors → Thriving at Work” pathway in the social embeddedness model of thriving at work in nursing. It shows that voice behaviors partially mediate the relationship between psychological empowerment and thriving at work. This finding provides a basis for nurse managers to develop intervention strategies that enhance nurses’ positive work experiences and improve the quality of medical services. Clinical trial number Not applicable.